2017
DOI: 10.3390/app7030237
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Prolonged-Release Drug Delivery System with Magnolol Loaded in Amino-Functionalized Mesoporous Silica

Abstract: Magnolol (MG) is a small-molecule neolignan polyphenolic compound isolated from the genus Magnolia. The anti-inflammatory, anti-oxidative, anti-diabetic, anti-tumorgenic, anti-neurodegenerative, anti-depressant and anti-microbial properties of MG are well documented in recent literature. These fascinating multiple biological activities of MG encourage research about the development of new delivery and administration approaches able to maximize its potential benefits. This study describes the amino-functionaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
(59 reference statements)
0
11
0
1
Order By: Relevance
“…For the solid dispersion prepared by MG and croscarmellose sodium (1: 5), the in vitro cumulative dissolution rate of MG reached 80.66% at 120 min, which was 6.9 times that of the raw MG (11.74%) (Tang et al, 2016). Stefanache et al incorporated MG into the pores of amino-functionalized mesoporous silica particles to increase the dosage of MG and delay its release (Stefanache et al, 2017a).…”
Section: Bioavailability and Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the solid dispersion prepared by MG and croscarmellose sodium (1: 5), the in vitro cumulative dissolution rate of MG reached 80.66% at 120 min, which was 6.9 times that of the raw MG (11.74%) (Tang et al, 2016). Stefanache et al incorporated MG into the pores of amino-functionalized mesoporous silica particles to increase the dosage of MG and delay its release (Stefanache et al, 2017a).…”
Section: Bioavailability and Formulationmentioning
confidence: 99%
“…In recent years, the bioavailability of MG has been significantly improved by various formulations including solid dispersion ( Ochiuz et al, 2016 ; Tang et al, 2016 ; Stefanache et al, 2017b ; Stefanache et al, 2017a ; Li et al, 2019 ), phospholipid complex ( Liu et al, 2020 ), liposome ( Chen, 2008 ; Chen, 2009 ; Shen et al, 2016 ), nanoparticles ( Wang et al, 2011 ), emulsion ( Sheng et al, 2014 ), mixed micelles ( Shen H et al, 2018 ; Ding et al, 2018 ), β-cyclodextrin inclusion compound ( Qiu et al, 2016 ), and Zr-based organometallic framework ( Santos et al, 2020 ) ( Table 3 ).…”
Section: Bioavailability and Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tamanna and Yu [13] loaded the antimicrobial rifampicin on PDA microspheres and found that the system maintained high stability at an acidic pH. This material has garnered important interest in the application of the controllable release of drugs as it can be governed by the responsivity of the molecular chains or the surface charge in reaction to pH [14][15][16][17]. Moreover, studies have shown that PDA can absorb ultraviolet light, which is why it is widely used in the preparation of UV-shielding composites [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Từ khóa-MCM-41, nano silica, vật liệu mao quản trung bình. trúc lỗ xốp trung bình và thể tích chứa lớn là một trong những loại MSNs tiêu biểu, được xem là hạt tải dược liệu hiệu quả bởi khả năng hấp phụ thuốc với dung lượng cao và đáp ứng nhả thuốc chính xác, đem lại kết quả điều trị cao [5][6][7][9][10][11]. Do đó, mục tiêu của hướng nghiên cứu là chế tạo vật liệu MCM-41 và khảo sát động học của quá trình hấp phụ Rhodamine B để xác định các thông số hấp phụ và các yếu tố ảnh hưởng đặc trưng đến quá trình hấp phụ nhằm xác định được dung lượng hấp phụ tối đa cũng như điều kiện tối ưu để đạt được điều đó, tạo tiền đề cho việc nghiên cứu tiếp theo trong ứng dụng làm chất tải thuốc đặc hiệu.…”
unclassified